Dunia Pendidikan: Epistimologi Pendidikan Anak Usia Dini Dalam Perspektif Maria Montessori - Alim Usman, A’zhami; Usman; Puji Azizah, Faras (TANJAK, 2024)
The purpose of this study is to examine the epistemology of early childhood education according to Maria Montessori. The literature review method is used to collect information from the literature related to this topic, with the type of study of the thoughts of figures. This article discusses four important points in Montessori's view of early childhood education, namely learning methods, learning models, curriculum, and views on early childhood. The result of this research is that Montessori emphasizes giving children the freedom to explore and learn through direct experience, with guidance from teachers who act as facilitators. Learning methods and models. Montessori also aims to strengthen children's ability to develop skills and individual potential, using appropriate educational aids and a supportive environment. The Montessori curriculum is designed to meet the needs and interests of individual children, emphasizing learning through direct experience and the development of social and emotional skills.